Ocorrência clínica da ehrlichiose monocítica equina e pesquisa de formas jovens de trematódeos em Heleobia spp. (Mollusca: Hydrobiidae) em terras baixas da encosta do Sudeste, RS - Coimbra, Helen Silveira (2010)
The equine monocytic ehrlichiosis (EME) is an infectious diseases caused by the Neorickettsia risticii. It present seasonal peaks, occurring hot of the year at the time and in subject to flooding regions. The transmission is oral way propagated for trematodes vectors. The disease has been told and diagnosed as cause of diarrhea in equinos not surrounded in the South region of the State. This study have as objective to tell cases of EME in the Rio Grande do Sul as well as the possible vectors of the disease. During the period of 2006 the 2009 had been carried through collections of vectors, clinical data and blood of animals with clinical case, in Rio Grande, Santa Vitória do Palmar, Arroio Grande and Palmares do Sul. The blood samples had been submitted the extraction and search of the DNA of the N. risticii through the PCR, and the joined vectors had been submitted the identification. In the period of November of 2006 the November of 2009 collected 16 samples of blood of animals. One of the horses was positive in the PCR for N. risticii with frequency of 6.6%. A total of 16864 snails of the Heleobia sort and a total of 357 insects of the classified Odonata Order had been collected in suborder Zigoptera and Anisoptera. Two species of Heleobia were identified, H. piscium and H. robusta. Three distinct morphologic types of cercariae had been found in the snails, as well as two morphologic types of metacercariae. The frequency of parasitism of trematodes in the snails to reach 12.83% of 1671 dissected snails. Only by suborder Anisoptera metacercariae phase was found in a 5.3% frequency. Through this study it is reaffirmed that the south region of Brazil presents ecological characteristics that must contribute with the endemic and seasonal character of the disease.